Infiltration as post-processing of laser sintered metal parts - Dück, J.; Niebling, Frank; Neeße, T.; Otto, Andreas (Powder Technology, 2004)
Laser sintering of metal parts is an additive production method applied in the field of rapid prototyping and rapid tooling. Direct metal laser sintering (DMLS) is a variant of the laser sintering processes. Metal powder is locally molten in this process and parts are built from layers. A fast laser sintering process, which is economically favourable, results in porous metal parts. For a technical application as e.g. the production of injection moulds for plastic parts, the surface has to be dense at a defined quality. A post-processing via infiltration is a possible solution for creating such surfaces. This paper describes the results of a study of the infiltration process: A model for describing the infiltration behaviour has been developed and validated through experiments. © 2004 Elsevier B.V. All rights reserved.
LFT Import::2019-07-16 (1059)
Keywords: Infiltration; Laser sintering; Rapid prototyping